CLIL na educação básica : uma metapesquisa sobre a produção de conhecimento acerca da abordagem CLIL - Torres, Paulo Cezar Lira (2024)
The number of bilingual schools in Brazil has increased in recent years, generating growing interest in the CLIL (Content and Integrated Language Learning) approach, according to Porcellato (2021). However, studies on its implementation in Brazilian schools are still scarce and focus on the use of English as an additional language (Landau, Albuquerque Paraná and Siqueira, 2021). Porcellato points to the potential of this approach in Brazil, despite the fact that there is little research on the subject. In the CLIL approach, one of the benefits that students gain, according to Gracia (2015), is motivation to learn both the content and the additional language. This research was motivated by my experience as an English language teacher and my interest in the CLIL approach. The aim of this study is to analyze the production of knowledge about the CLIL approach in Basic Education in Brazil through a metaresearch carried out with theses and dissertations from the CAPES Catalogue of Theses and Dissertations. Twenty papers were found from 2015 to 2023 and three of them made up the corpus of analysis of this research, since they discuss the CLIL approach in Basic Education in Brazil. The CLIL approach and the challenges in implementing this approach were analyzed, as well as the relationship between English language teaching and the CLIL approach. According to the analysis, the main potential of the CLIL approach is to make learning more meaningful by integrating content and language and to increase learner motivation. Lack of specific teacher training and lack of appropriate teaching materials were the main challenges pointed out. I hope that this study will encourage reflections on the importance of research into the CLIL approach, seeking to contribute to the strengthening of this field of research and action, as well as to the development of educational linguistics proposals that are meaningful for teachers and learners, taking into account the needs of the context and opening up new possibilities through education